Pengaruh Pertumbuhan Penjualan, Profitabilitas, Struktur Aktiva dan Ukuran Perusahaan Terhadap Struktur Modal Pada Perusahaan Pariwisata dan Perhotelan di BEI - Ryiadi, Nadia Puspawardhani (E-Jurnal Manajemen, 2014)
Financial management consists of three decisions, namely investment decisions, financing decisions and dividend policy. Financing decisions are influenced by capital structure. The capital structure is important to the company because it has the effect to the company's financial position, and the managers in a company should be able to know what factors affect the capital structure, it is intended that the company can maximize shareholder wealth. This study with the aim to determine the effect sales growth, profitability, asset structure and firm size on the capital structure. Location of the study is the tourism and hospitality companies in the period 2007-2011 IDX. The method of sample selection in this study is purposive sampling method, the sample is 10 samples. Methods of data collection is done through non - participant observation. The analysis technique used is multiple linear regression. The results showed that the sales growth, profitability, asset structure and firm size jointly have a significant effect . Sales growth has a significant negative effect on capital structure. Profitability significant positive effect on capital structure. Asset structure has a positive effect on capital structure. Firm size has a positive and significant impact on the capital structure .
Keywords: Debt Equity Ratio (DER); Growth Sale, Return On Equity (ROE); Asset Structure; Size.